2016
DOI: 10.1111/1471-0307.12336
|View full text |Cite
|
Sign up to set email alerts
|

Detection of adulteration by caprine body fat and mixtures of caprine body fat and groundnut oil in bovine and buffalo ghee using differential scanning calorimetry

Abstract: Differential scanning calorimetry was used to detect adulteration of pure ghee with caprine body fat when added singly (at 5, 10 and 15%) and in combination with groundnut oil (GNO) (at 5, 10 and 15%). Samples were analysed for transition behaviour in terms of crystallising and melting curves. When compared to pure ghee, adulterated ghee samples showed a shift in the midrange temperature of thermal curves, indicating the presence of foreign fats. The results revealed that the detection of adulteration was poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…According to literature, ghee is a lipophilic product with 99-99.5% lipids from which 46-47.8% is saturated fat, 36% monounsaturated and 18% polyunsaturated (Sharma et al, 2010;Sserunjogi et al, 1998). Ghee is also considered a good source of lipophilic vitamins (Upadhyay et al, 2017a), especially vitamin A and E (Antony et al, 2018), and conjugated linoleic acid -CLA (Food and Agriculture Drganization of the United Nations, 2013; Mehta et al, 2015;Upadhyay et al, 2017b), which is a ruminant trans fatty acid (rTFA) that has exhibited health benefits, both in vitro and in vivo (Galvín et al, 2016), such as anti-obesity, anti-carcinogenic, anti-atherogenic, anti-diabetic, anti-mutagenic, anti-hypertensive, immunomodulatory, apoptotic and osteosynthetic (Hur et al, 2017;Koba & Yanagita, 2014;Serafeimidou et al, 2013;Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to literature, ghee is a lipophilic product with 99-99.5% lipids from which 46-47.8% is saturated fat, 36% monounsaturated and 18% polyunsaturated (Sharma et al, 2010;Sserunjogi et al, 1998). Ghee is also considered a good source of lipophilic vitamins (Upadhyay et al, 2017a), especially vitamin A and E (Antony et al, 2018), and conjugated linoleic acid -CLA (Food and Agriculture Drganization of the United Nations, 2013; Mehta et al, 2015;Upadhyay et al, 2017b), which is a ruminant trans fatty acid (rTFA) that has exhibited health benefits, both in vitro and in vivo (Galvín et al, 2016), such as anti-obesity, anti-carcinogenic, anti-atherogenic, anti-diabetic, anti-mutagenic, anti-hypertensive, immunomodulatory, apoptotic and osteosynthetic (Hur et al, 2017;Koba & Yanagita, 2014;Serafeimidou et al, 2013;Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in other studies, it has been observed that components with a higher melting point display faster crystallization (Che Man et al, 1999). Other researchers detected the adulteration of caprine body fat at 5% level in bovine milk fat (ghee) using a DSC technique that the midrange temperature of isothermal curves was significantly different that displaced the crystallization region and indicated the presence of foreign fats (Upadhyay et al, 2017).…”
Section: Resultsmentioning
confidence: 71%
“…10 The reason that attracts ghee adulteration among traders is for increasing the higher cash income. Common detection methods for cheaper edible oils in ghee are chromatographic methods, [11][12][13][14][15][16] spectroscopic methods, 5,17,18 thermal analysis methods, 19 and physicochemical methods. [20][21][22][23] All these methods are time-consuming, requiring expertise and sample preparation for routine analysis.…”
Section: Introductionmentioning
confidence: 99%